SHIPPING AND FANSERVICE IN THE BOYS LOVE (BL) SERIES CONSUMPTION EXPERIENCE BY THE BRAZILIAN FANDOM - Torres, Igor Leonardo de Santana (Vivência: Revista de Antropologia, 2023)
Just as the idol shipping culture is important in the consumption and celebration of K-pop culture, shipping (practice of pairing fictional characters or media personalities, placing them into sexual or romantic relationships, or supporting already existing pairs) and fanservice (an entertainment practice for fans that consists of the performance of intimacy among celebrity couples created and supported by the fandom) are defining and distinctive elements of the Thai “boys love” (BL) industry and its transnational fandom. I will discuss these phenomena in the consumption experience of BL series by the Brazilian fandom and present their operation among the fans with whom I researched, paying attention to their forms of fanservice consumption and shipping practice. The results presented come from my master's research, in which, based on the digital ethnographic method, I observed and interacted with fans on Twitter and Telegram for nine months. I conclude, among other things, that the practice of shipping and the consumption of fanservice are heterogeneous in fandom and are embroiled in moral disputes. Keywords: BL Series; Brazilian BL Fandom; Fanservice; Shipping.